Authors of their own lives : intellectual autobiographies - Berger, Bennett M.; Bendix, Reinhard (Online access: California Digital Library UC Press E-Books Collection, 1982-2004 (Open Access), 1990)
Contains autobiographies by Dennis Wrong, David Riesman, James S. Coleman, Joseph Gusfield, Andrew M. Greeley, Bennett M. Berger, Dean MacCa.